The role of lipid metabolism in osteoporosis: Clinical implication and cellular mechanism - Jing Zhang; Wenhui Hu; Zhi Zou; Yuheng Li; Fei Kang; Jianmei Li; Shiwu Dong (Genes and Diseases, 2024)
In recent years, researchers have become focused on the relationship between lipids and bone metabolism balance. Moreover, many diseases related to lipid metabolism disorders, such as nonalcoholic fatty liver disease, atherosclerosis, obesity, and menopause, are associated with osteoporotic phenotypes. It has been clinically observed in humans that these lipid metabolism disorders promote changes in osteoporosis-related indicators bone mineral density and bone mass. Furthermore, similar osteoporotic phenotype changes were observed in high-fat and high-cholesterol-induced animal models. Abnormal lipid metabolism (such as increased oxidized lipids and elevated plasma cholesterol) affects bone microenvironment homeostasis via cross-organ communication, promoting differentiation of mesenchymal stem cells to adipocytes, and inhibiting commitment towards osteoblasts. Moreover, disturbances in lipid metabolism affect the bone metabolism balance by promoting the secretion of cytokines such as receptor activator of nuclear factor-kappa B ligand by osteoblasts and stimulating the differentiation of osteoclasts. Conclusively, this review addresses the possible link between lipid metabolism disorders and osteoporosis and elucidates the potential modulatory mechanisms and signaling pathways by which lipid metabolism affects bone metabolism balance. We also summarize the possible approaches and prospects of intervening lipid metabolism for osteoporosis treatment.